Efficiency of pheromone traps new and used on the capture of cotton boll weevil - Aquino, Ítalo Souza; Ramalho, Francisco de S.; Jesus, Fernando M. M.; Guevara, Luis A. Campos (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out to determine the efficiency to pheromone traps, both news and used, on the capture of the cotton boll weevil (Anthonomus grandis (Coleoptera: Curculionidae). A factorial (2 x 2 x 2) design in randomized blocks was used where the factors were: 1. type of trap (new and used); 2. period (three and seven days), and 3. insecticide (with and without), in ten replications. The insecticide used was Unden-Baygon (Propoxur 10%). The results obtained show that the pheromone traps used (dark funnel and bulb) are as efficient as the now ones on the capture of A. grandis, and that the insecticide strips increase the efficiency of the traps. The data show that besides the cotton boil weevil the phoromone traps capture other arthropods from the orders: Homoptera, Hymenoptera, Diptera, Lopidoptera and Araneida. The spiders spin webs in the trap funnel orifice which prevent the entry into the bulb and lower the number of insects captured.
Keywords: Anthonomus grandis; arthropods; grandlure; traps